Participação da enzima conversora de angiotensina 2 na fisiopatologia do sistema cardiovascular: papel nos efeitos do treinamento físico e na hipertensão arterial - Marilda Luz de Andrade de Maria (2015)
Clinical and experimental studies have shown that the renin-angiotensin system plays a key role in maintaining the homeostasis and that activation of endogenous angiotensin-converting enzyme 2 (ACE2) results in various beneficial effects in the cardiovascular system. Recently, a new ACE2 activator, named Diminazene Aceturate (DIZE), was discovered. This present studyevaluated the actions of this compound in cardiovascular and renal parameters of rats submitted to physical training or renovascular hypertension, as well as the mechanisms of action underling the vasodilation of isolated aortic rings. For this, Wistar rats were submitted to swimming training or to 2-kidney 1-clip surgery to induce renovascular hypertension. Animals were treated for 4 weeks with saline, captopril or DIZE by gavage. The results showed that DIZE did not interfere in the cardiac physiological hypertrophy induced by physical training.DIZE caused a significant decrease in blood pressure similar to the hypotensive effect induced by captopril in hypertensive rats. In addition, this compound also prevented the development of cardiac hypertrophy, cardiac fibrosis and renal dysfunction provoked by hypertension. The isolated vessels technique revealed that the vasodilatory effects of DIZE are dependent on Mas receptor and nitric oxide release. Thus, these data suggest that DIZE plays an important role in the homeostasis of the cardiovascular and renal systems, likely by a mechanism involving Mas and nitric oxide.